2013
DOI: 10.1371/journal.pone.0054944
|View full text |Cite
|
Sign up to set email alerts
|

Serum Glucose and Fructosamine in Relation to Risk of Cancer

Abstract: BackgroundImpaired glucose metabolism has been linked with increased cancer risk, but the association between serum glucose and cancer risk remains unclear. We used repeated measurements of glucose and fructosamine to get more insight into the association between the glucose metabolism and risk of cancer.MethodsWe selected 11,998 persons (>20 years old) with four prospectively collected serum glucose and fructosamine measurements from the Apolipoprotein Mortality Risk (AMORIS) study. Multivariate Cox proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 40 publications
0
21
1
Order By: Relevance
“…Further, in the meta-analyses of fasting glucose (16), the association between hyperglycemia and total prostate cancer incidence was attenuated and no longer statistically significant when restricted to studies that adjusted for BMI, like our study. In a prior study that incorporated repeated measures of glucose and fructosamine, fructosamine, but not glucose, was inversely associated with prostate cancer incidence; further, there was no significant association when men in the highest tertile of both biomarkers were compared with men in the lowest tertile of both biomarkers (32). Our findings for individual glycemia biomarkers and joint categories of these biomarkers are consistent with prior literature suggesting either no association, or a possibly modest inverse association between hyperglycemia and total prostate cancer incidence.…”
Section: Discussionmentioning
confidence: 90%
“…Further, in the meta-analyses of fasting glucose (16), the association between hyperglycemia and total prostate cancer incidence was attenuated and no longer statistically significant when restricted to studies that adjusted for BMI, like our study. In a prior study that incorporated repeated measures of glucose and fructosamine, fructosamine, but not glucose, was inversely associated with prostate cancer incidence; further, there was no significant association when men in the highest tertile of both biomarkers were compared with men in the lowest tertile of both biomarkers (32). Our findings for individual glycemia biomarkers and joint categories of these biomarkers are consistent with prior literature suggesting either no association, or a possibly modest inverse association between hyperglycemia and total prostate cancer incidence.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, the relationship between diabetes and cancer is yet to be definitively ascertained. Two recent studies have suggested a direct involvement of hyperglycaemia in the glucose metabolism-cancer relationship [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity [11, 2123] and dietary fat intake [30–32] may also affect subtype development via hormonal modulation, increased oxidative stress and inflammation [22]. Similar roles have been indicated for circulating glucose [17, 33, 34]. Therefore, increased GGT associated with increased risk of breast cancer may partly be acting as a marker of these metabolic disorders.…”
Section: Discussionmentioning
confidence: 98%